Reciprocal frame structures - Popovic, Olga (1996)
This thesis attempts an investigation of the Reciprocal Frame (RF) structure from the architectural point of view. The Introduction (Chapter 1) sets out the research subject and introduces the reader to the RF structure. Chapter 2 investigates the origin of the structure and offers a survey of similar types of systems used throughout human history. Also, a review of 'kinetic' forms of architecture is presented. Chapter 3 investigates Japanese RF construction and the possible reasons for the emergence of the system in Japan as early as the 12th century. Chapter 4 examines the potential of the system for modular construction of both temporary and permanent RF buildings, with a review of RF modular buildings constructed in the UK. Chapter 5 explores different RF morphologies on a student project case study, as well as their design experiences and opinions when using the RF system. More practical issues regarding the RF are presented in Chapter 6 which investigates the parameters which define the 2-dimensional and 3-dimensional geometry of the system and their variation, methods for simplifying the CAD presentation of the structure, alternative covering systems, and the possibility of using the RF as a retractable roof. Chapter 7 offers conclusions and aspects of future research on the system. The Appendices at the end include: two types of questionnaires and the complete transcribed interviews used to examine the students' design experiences and opinions, a routine in AutoLISP written by the author which simplifies the CAD presentation of the RF, and copies of the five Conference papers published using the findings of this research project.